Magnetic resonance imaging findings in adnexial torsion - Trindade,Ronald Meira Castro (2010)
ABSTRACT Adnexial torsion is an unusual event, but a major cause of abdominal pain in women. It is often associated with ovarian tumor or cyst, but can occur in normal ovaries, especially in children. The twisting of adnexial structures may involve the ovary or tube, but frequently affects both. In most cases, it is unilateral, with slight predilection for the right side. In imaging findings, increased ovarian volume and adnexial masses are observed, with reduced or absent vascularization. In cases of undiagnosed or untreated complete twist, hemorrhagic necrosis may occur leading to complications; in that, peritonitis is the most frequent. Early diagnosis helps preventing irreversible damage with conservative treatment, thereby saving the ovary. Limitations in performing physical examination, possible inconclusive results in ultrasound and exposure to radiation in computed tomography makes magnetic resonance imaging a valuable tool in emergency assessment of gynecological diseases. The objective of this study was to report two confirmed cases of adnexial twist, emphasizing the contribution of magnetic resonance imaging in the diagnosis of this condition.